Edukasi Penanganan Kasus Bullying Pada Mahasiswa Peserta Kampus Mengajar KM 7 - Abunawas Abunawas; Muhammad Tahir (Journal of Community Development, 2024)
Bullying in the world of education is no longer something new, especially at the primary and secondary school levels, both physically and psychologically, which results in the emergence of trauma by victims of bullying. The aim of this Community Service (PKM) activity is to educate junior high school (SMP) students at SMPN 5 Sungai Raya about bullying and efforts to avoid bullying as well as efforts to restore trauma to victims of bullying. The activity was carried out using an offline lecture method accompanied by illustrations of techniques for reporting bullying in the school environment. The activity was attended by 50 students, school teachers and students who received placements as campus teaching ambassadors (KM 7) at the school. Activity evaluation is carried out by giving questionnaires to participants regarding the educational material presented, which is filled out before and after the activity. The evaluation results showed an increase in participants' comprehension abilities from an average of 60% to 90%.